The problems of development of Family business in modern economy. (Journal of Economic Research & Business Administration, 2015)
This article discusses one of the new ways of rendering all possible assistance to small and medium-sized businesses, that is a family business. Considered its essence, development factors and features are also considered as the main parameters of the effective management of the family business problems to be solved for the transfer of business from one generation to another. Author analyses problems of developing small family businesses, it’s success factors, conditions, in what in Kazakhstan can be recovered the traditions of family business and can be developed new family business systems, that show a big efficiency and stability in the many regions of the world, shows the way of development and features of effective management of family business, substantiate the government help to the family business. Also in the article said that the model of effective management of family business can be developed like evolution of the system of family business – relations and mutual relations of family business and government, that family companies are purposeful and vital segment of national economics, they can make even more significant contribution in getting stable growth and competitiveness, if they get proper support.
Keywords: small family business; problems of family business; transfer of business from one generation to another; model of the effective management of the family business